Panel Testing Of Sputum Smear Microscopy Of National Tuberculosis Reference Laboratories In Saarc Region: 2003-2010 - Jha, KK; Thapa, B; Salhotra, VS; Afridi, NK (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2012)
Introduction: Quality assured sputum smear microscopy is a priority for Tuberculosis Control Programme to be successful to meet the global TB targets of 70% case detection and 85% treatment success rate. The SAARC TB Reference Laboratory has been conducting Panel Testing under External Quality Assurance Sputum Smear Microscopy for National TB Reference Laboratories of SAARC Member States to strengthen the Sputum Smear Microscopy. The study aims to review and analyse the Panel Testing for National Reference Laboratories of SAARC Member States. Methodology: The reports of seven rounds (2003-2010) of Panel Tests were collected and data from these reports was compiled and analysed. Results: Seven rounds of Panel Testing in the region have been completed since 2003 and ten TB Reference Laboratories within eight Member States participated. Afghanistan has been participating since 2007. Seven hundred and seventy-eight panel test slides were dispatched to and read by the participating laboratories and percentage agreement was 98.07%. Percentage agreement of individual participating laboratories varied from 87.50 to 100%. Fourteen minor errors and one major error (high false positive) were also observed with sensitivity and specifi city ranging from 90.90 to 100% and 83.33 to 100%, respectively. Conclusion: Panel Testing within the SAARC TB Laboratory network is extremely doing well. The success of TB control programmes in the SAARC Member States is refl ected by the excellent Panel Testing within the SAARC TB Laboratory Network. Continuation and improvement of External Quality Assurance of Sputum Smear Microscopy, introduction of External Quality Assurance of culture & drug susceptibility testing along with the introduction of recent diagnostic tests within the region is necessary to fi ght against TB. DOI: http://dx.doi.org/10.3126/saarctb.v8i1.5889 SAARCTB 2011; 8(1): 31-35